ERK1/2-Dependent Vascular Endothelial Growth Factor Signaling Sustains Cyst Growth in Polycystin-2 Defective Mice - SPIRLI, CARLO (2009)
BACKGROUND & AIMS: Severe polycystic liver disease can complicate adult dominant polycystic kidney disease, a genetic disease caused by defects in polycystin-1 (Pkd1) or polycystin-2 (Pkd2). Liver cyst epithelial cells (LCECs) express vascular endothelial growth factor (VEGF) and its receptor, VEGFR-2. We investigated the effects of VEGF on liver cyst growth and autocrine VEGF signaling in mice with Pkd1 and Pkd2 conditional knockouts. METHODS: We studied mice in which Pkd1 or Pkd2 were conditionally inactivated following exposure to tamoxifen; these mice were called Pkd1(flox/−):pCxCreER (Pkd1KO) and Pkd2(flox/−):pCxCreER (Pkd2KO). RESULTS: Pkd1KO and Pkd2KO mice developed liver defects; their LCECs expressed VEGF, VEGFR-2, hypoxia-inducible factor (HIF)-1α, phosphorylated extracellular signal–regulated kinase 1/2 (pERK1/2), and proliferating cell nuclear antigen (PCNA). In Pkd2KO but not Pkd1KO mice, exposure to the VEGFR-2 inhibitor SU5416 significantly reduced liver cyst development, liver/body weight ratio, and expression of pERK and PCNA. VEGF secretion and phosphorylation of ERK1/2 and VEGFR-2 were significantly increased in cultured LCECs from Pkd2KO compared with Pkd1KO mice. Inhibition of protein kinase A (PKA) reduced VEGF secretion and pERK1/2 expression. Addition of VEGF to LCECs from Pkd2KO mice increased phosphorylated VEGFR-2 and phosphorylated mitogen signal-regulated kinase (MEK) expression and induced phosphorylation of ERK1/2; this was inhibited by SU5416. Expression of HIF-1α increased in parallel with secretion of VEGF following LCEC stimulation. VEGF-induced cell proliferation was inhibited by the MEK inhibitor U1026 and by ERK1/2 small interfering RNA. CONCLUSIONS: The PKA–ERK1/2–VEGF signaling pathway promotes growth of liver cysts in mice. In Pkd2-defective LCECs, PKA-dependent ERK1/2 signaling controls HIF-1α–dependent VEGF secretion and VEGFR-2 signaling. Autocrine and paracrine VEGF signaling promotes the growth of liver cysts in Pkd2KO mice. VEGF inhibitors might be used to treat patients with polycystic liver disease.